EFEK ESKTRAK TANAMAN YANG BERBEDA TERHADAP MORTALITAS LARVA INSTAR III Musca domestica - Sakan, Gerson Yohanis Imanuel; Yuliani, Ni Sri (JURNAL KAJIAN VETERINER, 2021)
Chromolaena odorata and Lantana camara plants can be used as natural insecticides to control fly populations. Not only flies as vectors must be controlled but also their larvae are important for depopulation. This study aimed to examine the effect of different plant extracts on the mortality of third instar larvae of Musca domestica. A total of 36 petri dishes were used in this study, each containing 20 third instar larvae. Each extract treatment was divided into concentration levels of 15%, 30%, 45%, and 60%, and the control without extract was given. The extract was given using the feeding assay method. The larval mortality was observed for 24 hours after exposure to the extract. The results showed that concentrations of 15%, 30%, 45% C. odorata had higher mortality rates than L. camara, which was about 6.25,10.75, and 5. The average mortality of larvae by exposure to extracts of C. odorata and L. camara is almost the same value, namely 6,25, and 6 at the 60% concentration level. Both types of extracts studied had a mortality effect on larvae.